2023
DOI: 10.1111/dom.15152
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between genetic variability of adiponectin and leptin, glucose‐insulin system and subclinical atherosclerosis in patients with newly diagnosed type 2 diabetes. The Verona Newly Diagnosed Type 2 Diabetes Study 14

Chiara Zusi,
Alessandro Csermely,
Elisabetta Rinaldi
et al.

Abstract: Aim To evaluate the relationship of genetic variability of adiponectin (ADIPOQ), leptin (LEP) and leptin receptor (LEPR) genes with glucose‐insulin system and markers of subclinical atherosclerosis (ATS) in patients with newly diagnosed type 2 diabetes. Materials and methods In 794 subjects we performed: 1) euglycemic hyperinsulinemic clamp to assess insulin sensitivity; 2) mathematical modelling of a 5h‐OGTT to estimate β‐cell function; 3) resting ECG; 4) carotid artery and lower limb artery eco‐doppler sonog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…LA, a vital component of cell membranes, can alter membrane fluidity and regulate insulin sensitivity when integrated into phospholipids (28). High levels of LA can increase total and High Molecular Weight (HMW) adiponectin concentrations (29), A recent study showed a positive correlation between lipocalin levels and insulin sensitivity, lipocalin improves insulin sensitivity through its upregulation of IRS-2 in the liver and can lower blood glucose (30,31). This may be a mechanism by which LA reduces the risk of developing T2D.Additionally, LA is considered a PUFA in most Western diets, found in plant oils, nuts, and seeds (32).…”
Section: Discussionmentioning
confidence: 99%
“…LA, a vital component of cell membranes, can alter membrane fluidity and regulate insulin sensitivity when integrated into phospholipids (28). High levels of LA can increase total and High Molecular Weight (HMW) adiponectin concentrations (29), A recent study showed a positive correlation between lipocalin levels and insulin sensitivity, lipocalin improves insulin sensitivity through its upregulation of IRS-2 in the liver and can lower blood glucose (30,31). This may be a mechanism by which LA reduces the risk of developing T2D.Additionally, LA is considered a PUFA in most Western diets, found in plant oils, nuts, and seeds (32).…”
Section: Discussionmentioning
confidence: 99%